2021
DOI: 10.1159/000512796
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metformin and Vitamin D on Clinical Outcome in Cholangiocarcinoma Patients

Abstract: Background and Aims: In the last few years, there has been increasing interest in non-cancer medications and their potential anti-cancer activity. Data are not available in cholangiocarcinoma (CCA) patients. The aim of this study is to fill this gap by investigating the potential impact in terms of clinical outcome of the common non-cancer medications. Methods: All consecutive patients with CCAs were retrospectively identified from 7 Italian medical institutions. We investigated the role of intake of vitamin D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Ling et al studies showed that metformin exhibited a timedependent and dose-dependent antiproliferation effect on intrahepatic cell lines, by mechanisms containing apoptosis induction and cell cycle arrest [9]. Metformin intake after starting chemotherapy can improve the clinical outcome in advanced cholangiocarcinomas [24]. Metformin could change the metabolic status of cancer cells and reverse the Warburg effect via the inhibition of lactate dehydrogenase A(LDHA), which was overexpressed in CCA tissues and indicated a shorter survival time [11].…”
Section: Discussionmentioning
confidence: 99%
“…Ling et al studies showed that metformin exhibited a timedependent and dose-dependent antiproliferation effect on intrahepatic cell lines, by mechanisms containing apoptosis induction and cell cycle arrest [9]. Metformin intake after starting chemotherapy can improve the clinical outcome in advanced cholangiocarcinomas [24]. Metformin could change the metabolic status of cancer cells and reverse the Warburg effect via the inhibition of lactate dehydrogenase A(LDHA), which was overexpressed in CCA tissues and indicated a shorter survival time [11].…”
Section: Discussionmentioning
confidence: 99%
“…The remaining 34 studies were read in full, among which 13 studies did not investigate the efficacy of metformin on BTC, 4 studies did not explore risks or prognostic endpoints for BTC, 3 studies were cellular or animal studies, and 3 studies were duplicate reports of the same study. Finally, a total of 11 studies were included in the meta-analysis [ 21 , 22 , 23 , 24 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ]. The detailed process of study selection is presented in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A total of 11 studies involving 24,788,738 participants were finally included: two studies from each of the following countries: Italy, China, and the USA; and one study from each of the following countries: Thailand, Korea, Netherlands, Canada, and Sweden. Seven studies explored the effect of metformin on the risk of BTC [ 21 , 22 , 23 , 31 , 32 , 33 , 34 ], five explored its effect on OS [ 21 , 24 , 29 , 30 , 35 ], and two explored its effect on DFS [ 30 , 35 ]. The studies that reported median/mean age all ranged from 60 to 70.…”
Section: Resultsmentioning
confidence: 99%
“…Although the results of observational studies regarding the association between vitamin D status and liver cancer development are promising, they are still inadequate [ 31 ]. In a retrospective study of cholangiocarcinoma patients, vitamin D intake was associated with shorter disease-free survival in patients who underwent surgery [ 32 ]. This demonstrates the necessity for future prospective studies with a larger number of patients to investigate the association between vitamin D status and intake with hepatobiliary malignancy in patients with PSC.…”
Section: Discussionmentioning
confidence: 99%